(3GdGcJaGA ef JGQjN GdNdaGA Ch HJGQjN GdNdaGAs - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s
(3ChdgG (B:s
(3jHJOF HNdGaI GdeJbi HGddg GdChdi GdNdGaI HYO GdQGVi HGddg CNhg CejQ GdeDefjf GdeJbi HGddg s
(3BNQgG (B:s
(3MOjK Yf CHj SYjO GdNOQi SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd ai BNQ UdGJg Ch Mjf jfUQa (B:" (3SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf (B" s
(3Vef eLehY , JQJjHgG (B: (3GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B28 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CjGUhajG (B(2973) s
Keywords: (3GdJGQjNs